Global digital tool database for agroecological transitions - Dittmer, Kyle M.; Shelton, Sadie W.; Burns, Sessie A.; Wollenberg, Eva Karoline (2022)
This database contains a sample of global digital resources relevant to climate-informed agroecological transitions. Our purpose was to catalog relevant digital resources and assess their role in inclusive knowledge development, with special attention to farmers’ co-creation of knowledge for on-the-ground practices. To this end, we identified existing digital tools relevant to technical advisory and performance assessment and reviewed their functions (i.e., the purpose of using a tool) against indicators for exemplary features (i.e., the channels in which a user can engage with the tool) that could support socially inclusive, climate-informed agroecological transitions